Cloning and Functional Characterization of Octβ2-Receptor and Tyr1-Receptor in the Chagas Disease Vector, Rhodnius prolixus - Hana, Sam; Lange, Angela B. (Frontiers in Physiology, 2017)
Octopamine and tyramine, both biogenic amines, are bioactive chemicals important in diverse physiological processes in invertebrates. In insects, octopamine and tyramine operate analogously to epinephrine and norepinephrine in the vertebrates. Octopamine and tyramine bind to G-protein coupled receptors (GPCRs) leading to changes in second messenger levels and thereby modifying the function in target tissues and insect behaviour. In this paper, we report the cDNA sequences of two GPCRs, RhoprOctβ2-R and RhoprTyr1-R, have been cloned and functionally characterized from Rhodnius prolixus. Octopamine and tyramine each activate RhoprOctβ2-R and RhoprTyr1-R in a dose-dependent manner. Octopamine is one order of magnitude more potent than tyramine in activating RhoprOctβ2-R. Tyramine is two orders of magnitude more potent than octopamine in activating RhoprTyr1-R. Phentolamine and gramine significantly antagonize RhoprOctβ2-R, whereas yohimbine and phenoxybenzamine are effective blockers of RhoprTyr1-R. The transcripts of both receptors are enriched in the central nervous system (CNS) and are expressed throughout the adult female reproductive system. It has been shown in other insects that Octβ2-R is essential for processes such as ovulation and fertilization. We previously reported that octopamine and tyramine modulate oviducts and bursa contractions in R. prolixus. Our data confirm the importance of octopamine and tyramine signaling in the reproductive system of R. prolixus.